Damage Statistical Empirical Model for Fractured Rock under Freezing-Thawing Cycle and Loading. (29th October 2020) - Chen, Yifan; Lin, Hang; Wang, Yixian; Zhao, Yanlin
Abstract : The natural rock mass prevailingly exists in the form of a fractured rock mass, and freezing-thawing failure of the fractured rock mass is also frequently encountered during geotechnical projects in cold regions. The previous researches and reports in freezing-thawing field principally focused on intact rocks, while rock joints and fractures were rarely considered, which causes great inconvenience to the safety design and stability assessment of engineering. In response to the special climatic conditions of cold regions, the freezing-thawing damage and degradation mechanism of fractured rock were studied in this paper based on existing laboratory experiments and damage mechanics theory. Primarily, a brief review of the progressive damage process of rock in the conventional triaxial compression experiment was given, as well as the determination methods of four characteristic stresses in the prepeak curve. Then, from the microcosmic perspective, the maximum tensile strain yield criterion was used to reflect the microunit strength which was assumed to statistically satisfy the Weibull distribution, deriving the damage evolution equation of fractured rock under the freezing-thawing cycle and load conditions and quantificationally describing the damage evolution law. Consequently, the statistical empirical constitutive relation of fractured rock considering freezing-thawing and loading damages was established. Ultimately, by combining the existing conventional triaxial compression experimental data of freezing-thawing single fractured rocks with the determination methods of characteristic stresses, the relevant constitutive parameters were solved, and the theoretical constitutive relation curves of the fractured rock after freezing-thawing cycles were obtained, which were compared with the experimental results to verify the validity of the established empirical constitutive relation. The study findings can provide a theoretical basis for revealing the freezing-thawing failure mechanism of the fractured rock mass to some extent.